High-Dose vs. Low-Dose Dexamethasone in Patients With COVID-19: A Cohort Study in Rural Central America - Montalvan-Sanchez, Eleazar (2023)
To compare the clinical outcomes of a low dose dexamethasone strategy vs. a high-dose dexamethasone strategy in hypoxemic COVID-19 patients. A retrospective observational study comparing low-dose (8 mg) and high-dose dexamethasone (24 mg) of COVID-19 patients admitted from September 1, 2020 to October 31, 2020 in a hospital in Honduras. We included 81 patients with confirmed COVID-19 who required oxygen therapy. The mean age was similar between groups (57.49 vs. 56.95 years). There were more male patients in the group of 24 mg (p = 0.01). Besides, patients on the 24 mg dose had more prevalence of hypertension (p = 0.052). More patients in the 24 mg group had a higher rate of invasive mechanical ventilation (15.00% vs. 2.56%, p = 0.058). When evaluating the association between the high dose group and outcomes, we find no significant association with mortality, nosocomial infections, high flow mask, invasive mechanical ventilation, or the need for vasopressors. We find no significant differences in the Kaplan–Meier analysis regarding the survival (log-rank p-value = 0.315). We did not find significant differences between the use of 24 mg and 8 mg of dexamethasone in hypoxemic COVID-19 patients.